Reconstruction of the geological history of the Lithuanian Maritime Region from MIS 6 to MIS 3. (20th April 2022) - Bitinas, Albertas; Molodkov, Anatoly; Damušytė, Aldona; Grigienė, Alma; Satkūnas, Jonas; Šeirienė, Vaida; Šlauteris, Artūras
Abstract: The Lithuanian onshore section of the south-eastern Baltic Sea region, or the so-called Lithuanian Maritime Region (LMR) – a belt several tens of kilometres wide along the Baltic Sea coast – is characterised by a complicated Quaternary structure and many of unsolved problems related to stratigraphy and palaeogeography. The inter-till lacustrine sediments widespread in the middle part of the Pleistocene thickness play a key role in solving the mentioned problems. The primary inter-till sediments were attributed, as a single lithostratigraphic unit, to the late Saalian Glaciation (MIS 6, Pamarys Sub-Formation; according to the Lithuanian Quaternary Stratigraphic Scheme). Subsequent detailed investigations show that the investigated inter-till succession represents a more complicated sediment complex formed over a wide time interval from the Saalian ice sheet decay at the very end of MIS 6 to the beginning of severe climate cooling during MIS 4. This standpoint is confirmed by the results of a few series of OSL and IR-OSL datings of inter-till sediments, as well as by data of pollen and diatom analysis. The more detailed stratigraphic subdivision of the inter-till sedimentary complex offers a new significant insight into the regional stratigraphic scheme of the Quaternary. As a result of the mentioned investigations, a new original reconstruction of the palaeogeographic situation in the LMR during the MIS 6 – MIS 3 time span was carried out. The lowermost part of the investigated inter-till sediments, attributed to MIS 6, could be correlated with the third MIS 6 warming in Northern Eurasia about 155 ka ago. The reconstruction of the palaeoenvironmental changes starting from MIS 6 and lasting to MIS 3 shows that the Eemian Sea MIS 5e in age was absent in the LMR, while part of the south-eastern Baltic Sea region was covered by a continental ice sheet during MIS 4 and, possibly, the very beginning of MIS 3.